STORY TELLING PEMBANGUN KARAKTER DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SD MUHAMMADIYAH TELUK BETUNG KABUPATEN HULU SUNGAI UTARA - Hatmiah Hatmiah (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The application of story telling has been implemented so as to produce a disciplined and religious character. Story telling is an interesting method and is used by PAI teachers at Muhammadiyah Teluk Betung Elementary School. This is because the students are more interested in participating in learning. Based on this statement, research was carried out with a research focus that focused on the application of story telling in building character in Islamic Religious Education (PAI) subjects at Muhammadiyah Elementary School Teluk Betung which included disciplinary and religious characters, as well as the factors that influenced them. The subjects in this study were two Islamic religious education teachers at Muhammadiyah Teluk Betung Elementary School. The techniques used in data collection are interviews, observations, and documentaries. Then processed through the process of data reduction, data display, and data verification. Meanwhile, to analyze the data the author uses descriptive and qualitative analysis. Finally it can be concluded that 1) The application of story telling in building character in Islamic Religious Education (PAI) subjects at Muhammadiyah Elementary School Teluk Betung is illustrated in; a) PAI teachers have used story telling in learning. Many are obtained by students, one of which is the awakening of the character of student discipline. b) PAI teachers have used story telling in learning. Students get a lot, one of which is the awakening of students' religious character. 2) Factors that influence it, such as; a) PAI teachers have the ability to teach well. This is evidenced by the interest of students in following the learning process properly and the motivation of students to behave well. b) PAI teachers have been teaching him for a long time and are also very experienced in teaching. This is because the PAI teacher already understands very well the character of my students, so the method or method of teaching has been adjusted.